Methods of Early Childhood Education: Enhancing Education Quality through Fun Learning Approach - Mardyawati Y; Badruddin Kaddas (Journal of Research and Multidisciplinary, 2023)
Early childhood education requires appropriate learning methods to form a strong foundation in their development. Fun Learning is a fun and engaging learning method that can be used to achieve this goal. Fun Learning combines learning and play, and can be done through role-playing, playing with educational toys, reading stories, and singing and dancing. It is important for teachers to create a fun learning environment that captures the attention of children, and parents can also help in creating activities that can be done at home. Experts such as Piaget and Vygotsky have stated that the Fun Learning approach is suitable for young children and can improve their social, cognitive, and motor skills. However, the role of the teacher as a facilitator and guide is crucial in implementing the Fun Learning method to maximize children's learning outcomes. Research conducted by Gordon and Browne shows that the Fun Learning approach can increase the motivation and interest of young children in learning. Therefore, it is important for educators and parents to understand and effectively apply the Fun Learning method to help the development of young children.